2015
DOI: 10.11152/mu.2013.2066.171.muv
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the retrobulbar orbital fat tissue and optic nerve with strain ratio elastography

Abstract: Aim: The aim of this study was to evaluate the diagnostic performance of strain ratio elastography in the assessment of retrobulbar orbital fat tissue. Materials and methods: The retrobulbar fat tissue of 14 eyes in 14 participants was scanned by sonoelastography. All the participants had permanent vision loss secondary to glaucoma in at least one eye. The elasticity scores were determined and the strain ratio was based on the comparison of the average strain measured in the retrobulbar fat tissue around the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 8 publications
0
36
1
Order By: Relevance
“…In some studies, it has been reported that there is a connection between the tissue elasticity and histological features. Elastography is used successfully in prostate, lymph node, breast, thyroid, testis, renal and liver disease examination [12][13][14][15][16]. However, to the best of our knowledge, there has been no work in the previous literature that has investigated the optic nerve with elastography in MS patients.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…In some studies, it has been reported that there is a connection between the tissue elasticity and histological features. Elastography is used successfully in prostate, lymph node, breast, thyroid, testis, renal and liver disease examination [12][13][14][15][16]. However, to the best of our knowledge, there has been no work in the previous literature that has investigated the optic nerve with elastography in MS patients.…”
Section: Introductionmentioning
confidence: 81%
“…Histopathological research of the optic nerve in MS showed that prominent axonal loss occurs and the optic nerve cross-sectional area decreases after optic neuritis [6,20,21]. In recent studies significant correlations between the histopathological aspect and the tissue stiffness determined by elastography were established [12,13,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SE is observed by applying strain manually by the user and establishing the relative strain in a tissue with comparisons to its surrounding tissue [10,11]. Whereas, SWE simply uses a combination of shear waves, it measure the absolute value of the tissue and delivers tissue elasticity based on force values detected by the machine [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Although grayscale ultrasonography (US) is a noninvasive method that has been used to evaluate the eye structures for many years, elastography is a new technique and is not used as widely for the orbita and orbital structures as for other organs [6,7].…”
Section: Introductionmentioning
confidence: 99%